2020
DOI: 10.1093/geroni/igaa057.1883
|View full text |Cite
|
Sign up to set email alerts
|

Benevolent Ageism’s Relationship to Self-Compassion and Meta-Memory in Older Adults

Abstract: Benevolence directed towards older adults can cross the line between respect and overaccommodation that undermines their physical and cognitive capabilities (Mehrotra & Wagner, 2009); however, little research has examined the subtleties of the influence of benevolent ageism on older adults’ ratings of their own functioning. Because stereotypes about older adults include the decline of mental abilities, this study examined whether their (N= 155) experiences with benevolent ageism, or overaccommodative offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…However, these new, intended protective, policies challenged older adult's emotional wellbeing, limited social connectivity, and fostered isolation. Although not evident in our data, there is the risk that benevolent ageism might foster cognitive decline (Cohn‐Schwartz et al., 2022 ; Sublett & Bisconti, 2020 ; see also Giebel et al., 2021 , with respect to dementia). Additionally, the policies restricted individual autonomy, challenged established ways of communication, and consequently, increased anxiety.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, these new, intended protective, policies challenged older adult's emotional wellbeing, limited social connectivity, and fostered isolation. Although not evident in our data, there is the risk that benevolent ageism might foster cognitive decline (Cohn‐Schwartz et al., 2022 ; Sublett & Bisconti, 2020 ; see also Giebel et al., 2021 , with respect to dementia). Additionally, the policies restricted individual autonomy, challenged established ways of communication, and consequently, increased anxiety.…”
Section: Discussioncontrasting
confidence: 52%
“…Benevolent ageism has recently been recognized as a form of patronizing and over‐accommodating attitude towards older adults based on an age stereotype of impaired competence. Sublett and Bisconti ( 2020 ) found that this kind of ageism adversely impacted on older adults’ self‐compassion, which in turn influenced their appraisals of their cognitive abilities. People who had fewer experiences of benevolent ageism were found to have higher rates of self‐compassion and this resulted in better evaluations of their memory.…”
Section: Introductionmentioning
confidence: 99%
“…( 2012 ) showed, for example, that adults who self‐categorized themselves as older and expected their own memory to decline in old age performed worse on memory tests. A different study found that older adults with fewer benevolent ageist experiences had better evaluations of their memory abilities via self‐compassion (Sublett & Bisconti, 2020 ). However, less is known about the effects of perceived societal ageism in relation to subjective memory, especially during the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%